1986
DOI: 10.1111/j.1365-2133.1986.tb02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczematous reactions in atopic patients caused by epicutaneous testing with inhalant allergens

Abstract: To determine whether inhalant allergens could induce eczematous lesions we studied 17 patients with atopic eczema (with or without allergic rhinitis), 13 patients with allergic rhinitis without atopic eczema and 10 healthy control subjects. The allergens, birch pollen (Betula verrucosa) and house dust mite (Dermatophagoides pteronyssinus), were applied in aluminium chambers for 48 h on clinically normal skin. In 17 patients with atopic eczema, six epicutaneous test reactions of the delayed type to birch pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(65 citation statements)
references
References 18 publications
2
60
0
2
Order By: Relevance
“…The development of allergen patch tests indicated that antigens of house-dust mites were capable of inducing a delayed-in-time eczematous-type response, and that this involved elements of the immune response additional to IgE antibody [41,42]. As is the case with other atopic diseases, it is now evident that patients with the disorder may posess T-cells sensitized to specific mite allergens [43], and that T-cells are one of the major cell types that infiltrate the skin both in naturally occurring atopic dermatitis and in patch-test reactions [44]. Langerhans cells, the antigen-presenting cells of the skin, possess receptors for IgE antibody [45], and mite allergen has been found attached to these cells [46] which further indicates the overlap between IgE antibody production and cell-mediated immunity.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…The development of allergen patch tests indicated that antigens of house-dust mites were capable of inducing a delayed-in-time eczematous-type response, and that this involved elements of the immune response additional to IgE antibody [41,42]. As is the case with other atopic diseases, it is now evident that patients with the disorder may posess T-cells sensitized to specific mite allergens [43], and that T-cells are one of the major cell types that infiltrate the skin both in naturally occurring atopic dermatitis and in patch-test reactions [44]. Langerhans cells, the antigen-presenting cells of the skin, possess receptors for IgE antibody [45], and mite allergen has been found attached to these cells [46] which further indicates the overlap between IgE antibody production and cell-mediated immunity.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…tions could be induced by patch tests with environmental allergens (house-dust tnites, grass pollen) as a tnodel for this tnode of triggering AD (3,4,11,31), In these patients, as in LPRs, a significant infiltration of eosinophils in the skin was detected within 2-6 h. By means of monoclonal antibodies against eosinophil toxic proteins, it was shown that these eosinophils were preactivated and that most of their granule content was released into the surrounding tissue. Twenty-four hours after allergen challenge, eosinophils could be detected even in the epidermis.…”
Section: Eosinophils In Atopic Dermatitismentioning
confidence: 99%
“…As demonstrated by several groups in a number of patients, environmental allergens, e.g. those of grass pollen and house-dust mites, induce eczematous reactions when applied to the skin (4,11,31). Moreover, it was shown that skin contact with these allergens may result in a general exacerbation of AD (1,5,17,26,36).…”
mentioning
confidence: 99%
“…(12) reported the occurrence of positive patch test reactions to a variety of aeroallergens in patients with AD. Other studies investigating the possible role of contact allergy to aeroallergens in the pathogenesis of AD soon followed (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%